ANALISIS PENERAPAN PROTOKOL KESELAMATAN DAN KESEHATAN KERJA DI LINGKUNGAN SEKOLAH: STUDI LITERATUR PADA SEKOLAH ISLAM TERPADU - Septia, Rizka; Hidayat, Taufik; Hadiati, Eti; Junaidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The implementation of Occupational Health and Safety (OHS) protocols in schools is essential for fostering a safe, healthy, and productive learning environment. This study aims to analyze how OHS protocols are applied in Integrated Islamic Schools (SIT) by reviewing recent literature published between 2020 and 2025. Using a literature review method, this research identifies five key themes: integration of Islamic values, school leadership, student participation, institutional readiness, and social collaboration. The findings show that values such as amanah (responsibility), ihsan (excellence), and ukhuwah (brotherhood) strengthen the internalization of safety culture in SIT environments. Leadership that is transformational and religiously grounded plays a crucial role in shaping sustainable OHS practices. However, various systemic limitations, including lack of resources, contextual SOPs, and formal reporting systems, continue to hinder optimal implementation. This study concludes that OHS protocols in SIT require an adaptive, integrative, and values-based approach that aligns with the spiritual and structural uniqueness of Islamic education institutions.